PROFITABILITAS DAN FAKTOR-FAKTOR DETERMINAN - Asih Niati; Tri Rinawati (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2019)
To carry out its operations, companies need large funds for investment or production. The need for large funds is not only filled with own capital, but foreign capital (debt). The debt owed by the company must be managed so that it ultimately does not cause losses The debt ratio in financial statements shows how much assets are financed by debt. This ratio emphasizes the important role of debt financing in companies by showing the percentage of company assets supported by debt. The purpose of this study was to examine and analyze the effect of cash turnover, accounts receivable turnover and liquidity on the liquidity of manufacturing companies in the consumption sector for the period of 2013 - 2017. The population of this research is manufacturing companies engaged in the food and beverage sector listed on the Indonesia Stock Exchange in the period 2013 - 2017. The number of samples used in this study were 14 companies. The sample selection method used was purposive sampling. The analysis technique used is the Analysis of Multiple Linear Regression. The results of this study are that there is a significant negative effect between Cash Turnover on Liquidity and there is also a significant positive direction influence between Accounts Receivable Turnover and Liquidity. Likewise there is a significant positive direction between Liquidity to Profitability.